Business Administration and Business Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
Slow tourism is an emergent concept that investigates ways in which people can reject the tenets of mass tourism with its ever increasing velocity of consumption and expenditure. Instead, it offers way in which people can engage with local customs, institutions and people at a pace which is also less damaging to the environment. However, the facilities and services that such a form of tourism requires is little known to destination managers (although perhaps not to specific facility managers) in both the private and public sectors. In order to determine the extent to which understanding of this issue is widespread in Thailand, which is a country where the tourism industry is vital in maintaining the economy, and where a range of different types of tourism have become available. The province of Samut Prakan has been selected for this purpose and a convenience sample of 400 respondents was taken in a total of four different destinations using a questionnaire based on the UNWTO’s Recife Declaration on Slow Tourism. It is found that Thai slow tourists in the sample demonstrate some spiritual qualities in their desire for experiences that are not accounted for in the original declaration and it is suggested that this be adjusted accordingly.